Understanding Food: Principles and Preparation, 6th Edition - Amy Brown (Cengage Learning, 2018)
UNDERSTANDING FOOD: PRINCIPLES AND PREPARATION is your introductory guide to food, food preparation, food service and food science. Integrating these key topics with relevant information about nutrition and the food industry, this best-selling text gives you a thorough overview of the different dimensions of food principles and insight into the variety of career options available in the food industry.